Creep behaviour of Laser Powder Bed Fused alloy 718 - Sanchez, Salomé (2022)
Laser Powder Bed Fusion (LPBF) is characterised by high design flexibility and no tooling requirement. This makes LPBF attractive to many modern manufacturing sectors (e.g. aerospace, defence, energy and automotive). Nickel-based superalloys are crucial materials in modern engineering and underpin the performance of many advanced mechanical systems. Their physical properties (high mechanical integrity at high temperature) make them difficult to process via traditional techniques. Consequently, manufacture of nickel-based superalloys using LPBF has attracted significant attention.